2014
DOI: 10.4141/cjas2013-198
|View full text |Cite
|
Sign up to set email alerts
|

Feeding increasing dietary inclusions of extrudedBrassica junceacanola expeller-pressed cake on growth performance, carcass characteristics, and jowl fatty acids of growing-finishing pigs

Abstract: Zhou, X., Young, M. G., Zamora, V., Zijlstra, R. T. and Beltranena, E. 2014. Feeding increasing dietary inclusions of extruded Brassica juncea canola expeller-pressed cake on growth performance, carcass characteristics, and jowl fatty acids of growing-finishing pigs. Can. J. Anim. Sci. 94: 331–342. The energy value of canola meal is considered low because of its relatively higher fibre and depleted oil content. Brassica juncea is a novel canola species with thinner seed coat and reduced fibre, but twice the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
8
3
Order By: Relevance
“…The total glucosinolate level in B. napus CM fed in our trial (5.9 mol/g) was greater than the Canadian average of 3.9 mol/g (Rogiewicz et al, 2012). The glucosinolate level in B. juncea CM fed in our trial (12.3 mol/g) was greater than levels observed by Landero et al (2013;10.8 mol/g), Zhou et al (2014a;10.9 mol/g) and Le et al (2014;10.9 mol/g), but lower than levels observed by Collins et al (2011;15.9 mol/g) and Zhou et al (2013;12.5 mol/g). The main glucosinolates were progoitrin for B. napus and gluconapin for B. juncea.…”
Section: Effects Of Canola Speciescontrasting
confidence: 81%
See 4 more Smart Citations
“…The total glucosinolate level in B. napus CM fed in our trial (5.9 mol/g) was greater than the Canadian average of 3.9 mol/g (Rogiewicz et al, 2012). The glucosinolate level in B. juncea CM fed in our trial (12.3 mol/g) was greater than levels observed by Landero et al (2013;10.8 mol/g), Zhou et al (2014a;10.9 mol/g) and Le et al (2014;10.9 mol/g), but lower than levels observed by Collins et al (2011;15.9 mol/g) and Zhou et al (2013;12.5 mol/g). The main glucosinolates were progoitrin for B. napus and gluconapin for B. juncea.…”
Section: Effects Of Canola Speciescontrasting
confidence: 81%
“…The decreased carcass dressing in pigs fed B. juncea compared to B. napus CM in this trial could be due to a slight increase in the weight of the liver and thyroid in response to greater glucosinolate intake. Glucosinolate levels in B. juncea CM fed in our trial were greater than those observed in other recent experiments (Landero et al, 2013;Zhou et al, 2014a;Le et al, 2014). High glucosinolate intake increased liver weight in chickens (Woyengo et al, 2011) and liver and thyroid weight in pigs (Bourdon and Aumaître, 1990;Corino et al, 1991;Schöne et al, 1996).…”
Section: Effects Of Canola Speciescontrasting
confidence: 79%
See 3 more Smart Citations